2015
DOI: 10.5927/jjjd.25.201
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Hyoid Bone Position and Pharyngeal Airway Morphology before and after Orthognathic Surgery for Mandibular Prognathism

Abstract: Treatment to improve malocclusion in patients with skeletal mandibular protrusion often involves the combined use of surgical treatment in orthodontic treatment to improve not only occlusion but also facial appearance. Mandibular setback surgery is known to cause displacement of the hyoid bone and affect the morphology of the respiratory tract. However, although there have been previous reports regarding displacement of the body of the hyoid bone, few reports have verified hyoid bone rotation taking complex mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…The width of the airway decreases after mandibular setback in the area from the intermediate part of the soft palate to the posterior border of the base of the tongue, though there is no significant difference in the decrease of that in the area of the upper part the soft palate and the epiglottic vallecular [20]. The airway was decreased 2.24 mm around the uvula, 2.5 mm at the angle of the mandible, and 1.05 mm around the epiglottis after mandibular setback more than 8 mm [21]. As for the epiglottis, it is reported that the swallowing triangle, that composed of the top of the epiglottis, the posterior pharynx, and hyoid bone, moves postero-inferiorly, just after mandibular setback, though it returns at certain extent overtime [22].…”
Section: Discussionmentioning
confidence: 99%
“…The width of the airway decreases after mandibular setback in the area from the intermediate part of the soft palate to the posterior border of the base of the tongue, though there is no significant difference in the decrease of that in the area of the upper part the soft palate and the epiglottic vallecular [20]. The airway was decreased 2.24 mm around the uvula, 2.5 mm at the angle of the mandible, and 1.05 mm around the epiglottis after mandibular setback more than 8 mm [21]. As for the epiglottis, it is reported that the swallowing triangle, that composed of the top of the epiglottis, the posterior pharynx, and hyoid bone, moves postero-inferiorly, just after mandibular setback, though it returns at certain extent overtime [22].…”
Section: Discussionmentioning
confidence: 99%